2019
DOI: 10.1363/psrh.12123
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Life Planning and Contraceptive Action Planning for Privately Insured Women: The MyNewOptions Study

Abstract: 219CONTEXT: Although reproductive life planning (RLP) is recommended in federal and clinical guidelines and may help insured women make personalized contraceptive choices, it has not been systematically evaluated for effectiveness. METHODS:In 2014, some 984 privately insured women aged 18-40 who were not intending to become pregnant in the next year were randomly assigned to receive RLP, RLP with contraceptive action planning (RLP+) or information only (the control group). Women's contraceptive use, prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Studies focused on implementation in a clinical setting often mentioned the importance of taking a patient-centred approach, ensuring shared decision-making and balanced counselling, and aspects of motivational interviewing, which is a recognised behaviour change technique. The web-based ‘My New Options’ RLP incorporated action planning (19). This encourages a person to think in advance how to implement the desired behaviour and how to address challenges, reducing the cognitive load when these situations are faced (73).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies focused on implementation in a clinical setting often mentioned the importance of taking a patient-centred approach, ensuring shared decision-making and balanced counselling, and aspects of motivational interviewing, which is a recognised behaviour change technique. The web-based ‘My New Options’ RLP incorporated action planning (19). This encourages a person to think in advance how to implement the desired behaviour and how to address challenges, reducing the cognitive load when these situations are faced (73).…”
Section: Resultsmentioning
confidence: 99%
“…The four studies of digital RLPs’ acceptability (19, 20, 43, 51), found them to be an acceptable format, including in one study that included men (20). Respondents described an interactive, web-based format as easy to use and ‘desirable’ (19) with the majority reporting that they liked the online format (e.g. 75.3% in 43).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parent study tested the effectiveness of web-based interventions to assist insured self-identified women in making individualized contraceptive choices (ClinicalTrials.gov identifier:). 8 Study participants were members of Highmark Health plans in Pennsylvania and sampled from the Highmark enrollee database. Eligible self-identified women were aged 18-40, not intending pregnancy in the next 12 months, not surgically sterile (or current partner with vasectomy), sexually active with reported male partner(s), and had Internet access.…”
Section: Methodsmentioning
confidence: 99%